'What man art thou' imitation, masculinity, and homosociality in the poetry of Edward Herbert - Hardy, E (2019)
This thesis explores the way that practices of imitation informed early modern ideas about manhood and friendship in the poetry of Edward, Lord Herbert of Cherbury (1582?-1648). Through a series of case studies which situate Herbert’s verse in the homosocial networks in which it was composed, circulated, and read, it uses Herbert’s poetry as a lens to demonstrate the ways that imitation can be collaborative and dialogic, affirming social and familial relationships. Herbert’s poetry also demonstrates how ideas about multiplicity and an anxiety around malleability informed early modern thinking about gender and manhood.